Management an integrated approach - Gulati, Ranjay; Mayo, Anthony J.; Nohria, Nitin (Australia Cengage Learning, 2017)
The goal of Management: an integrated approach, 2nd Edition, is to prepare students for leadership positions in 21st century companies by addressing the many facets involved in answering one key question: How are leaders successfully managing competitive companies in the 21st century? Today's constantly changing business environment presents challenges and opportunities that are more dynamic and complex than ever before, requiring a clear understanding of the interactive nature of strategy, organizational design, and leadership. Management: an integrated approach, written by prominent Harvard management educators Ranjay Gulati, Anthony Mayo, and Nitin Nohria, is the only introductory management text on the market to address this challenge by taking an integrated and holistic approach to management, as opposed to a functional approach, making it more relevant to how today's organizations run. By demonstrating the interconnectivity among the three key pillars of management, students see how decisions impact strategic choices, organizational alignment, and leadership approaches, ultimately leading to the overall performance of the company. MindTap® for Gulati/Mayo/Nohria's Management: an integrated approach, has been completely revised and updated to incorporate a suite of new digital resources designed to facilitate and measure student success. This unique approach will develop a sustainable and successful leadership style, better preparing students for higher level courses and making them more marketable upon graduation. --Provided by publisher.
Part I: Setting the context for management -- 1. Introduction to Management -- 2. The Global Business Environment -- 3. Ethics and Corporate Social Responsibility -- Part II: Strategic perspective -- 4. Introduction to Strategy -- 5. Business-Level Strategy -- 6. Corporate-Level Strategy -- Part III: Organizational perspective -- 7. Organizational Structure and Design -- 8. Organizational Culture -- 9. Managing Human Capital -- 10. Performance Management -- 11. Organizational Change -- Part IV: individual perspective -- 12. Leadership in Organizations -- 13. Becoming a Leader: Knowing Yourself -- 14. Power and Influence -- 15. Decision-Making -- 16. Conflict & Negotiation -- 17. Leading Teams -- 18. Motivation -- 19. Communication -- 20. Networking.
Includes bibliographical references and indexes.
Keywords: Management; Industrial management; Business enterprises; Success in business